2010
DOI: 10.1039/b9nj00307j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and use of a surface-active initiator in emulsion polymerization under AGET and ARGET ATRP conditions

Abstract: A novel surface-active ATRP initiator disodium 4-(10-(2-bromo-2-methylpropanoyloxy)decyloxy)-4-oxo-2-sulfonatobutanoate (1a) has been designed and synthesized efficiently in three steps. The controlled radical emulsion polymerizations of methyl methacrylate (MMA) were realized in one step without any added surfactant under AGET and ARGET ATRP conditions, in which the initiator 1 functioned as both an ATRP initiator and a latex stabilizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Over the past two decades, there has been considerable interest in using controlled living radical polymerization techniques to prepare amphiphilic diblock copolymers in the form of nanoparticles in aqueous media via polymerization-induced self-assembly (PISA). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] PISA occurs in situ when a watersoluble homopolymer is chain-extended with an appropriate second monomer. The growing second block gradually becomes insoluble in the reaction solution, which drives in situ self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, there has been considerable interest in using controlled living radical polymerization techniques to prepare amphiphilic diblock copolymers in the form of nanoparticles in aqueous media via polymerization-induced self-assembly (PISA). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] PISA occurs in situ when a watersoluble homopolymer is chain-extended with an appropriate second monomer. The growing second block gradually becomes insoluble in the reaction solution, which drives in situ self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature survey, many previous studies [ 28 , 29 , 30 , 31 , 32 , 33 ] reported a well-controlled AGET ATRP of MMA in emulsion polymerization using the two-step method to synthesize polymers with a low polydispersity index (Ð), narrow experimental number-average molar mass (M n ), and high initiation efficiency. For instance, Cheng et al [ 34 ] performed a well-controlled emulsion AGET ATRP of MMA using a surface-active initiator. Li [ 35 ] conducted a two-step AGET ATRP of MMA and good colloidal stability for both microemulsion and emulsion polymerization was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a variety of control methodologies for radical polymerizations have been developed with atom transfer radical polymerization, reversible addition–fragmentation chain transfer (RAFT) polymerization, and nitroxide‐ mediated polymerization being by far the most prominent techniques. A high level of control during the polymerization as well as the ability to tune the polymer properties is easily reached, making these techniques highly favorable for the synthesis of complex polymer architectures.…”
Section: Introductionmentioning
confidence: 99%